The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s1368980013002139
|View full text |Cite
|
Sign up to set email alerts
|

Review Article Relationships between intuitive eating and health indicators: literature review

Abstract: Objective: To review the peer-reviewed literature on relationships between intuitive eating and health indicators and suggest areas of inquiry for future research. We define the fundamental principles of intuitive eating as: (i) eating when hungry; (ii) stopping eating when no longer hungry/full; and (iii) no restrictions on types of food eaten unless for medical reasons. Design: We include articles cited by PubMed, PsycInfo and Science Direct published in peer-reviewed journals or theses that include 'intuiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
166
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 40 publications
(161 reference statements)
15
166
2
8
Order By: Relevance
“…13 Non-diet approaches are proven to support long term behavior changes and healthful eating and living habits. 10,12,13 The results of a New Zealand study with 1,600 women also confirmed a negative correlation between BMI and intuitive eating scores. 14 Women who reported trying to lose weight (n=398) at the start of the study were significantly heavier (p<.001) at the end of the 3 years compared to the women who reported weight maintenance (n=423) or no attempt at weight loss (n=153).…”
Section: Intuitive Eatingmentioning
confidence: 66%
See 3 more Smart Citations
“…13 Non-diet approaches are proven to support long term behavior changes and healthful eating and living habits. 10,12,13 The results of a New Zealand study with 1,600 women also confirmed a negative correlation between BMI and intuitive eating scores. 14 Women who reported trying to lose weight (n=398) at the start of the study were significantly heavier (p<.001) at the end of the 3 years compared to the women who reported weight maintenance (n=423) or no attempt at weight loss (n=153).…”
Section: Intuitive Eatingmentioning
confidence: 66%
“…This is consistent with other studies which have a confirmed negative correlations between intuitive eating and BMI. 10,52,53 There was no significant difference between the intuitive eating groups and HEI scores. Nor was IES-2 observed to be correlated to HEI scores.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…When dieting and intuitive eating programmes are compared, greater short-term weight loss is seen with dieting, although the sustainability of this is questionable [43,56].…”
Section: Consistency Of Findingsmentioning
confidence: 99%